Karakteristik Campuran Aspal HRS-WC Dengan Menggunakan Agregat Batu Gunung Kandora Dengan Variasi Agregat Halus Di Kabupaten Tana Toraja - Michael Mangontan; Syahrul Sariman; Abdul Rahim Nurdin (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Hot Rolled Sheet (HRS) is one type of hot asphalt mixture consisting of a mixture of fine aggregate, coarse aggregate, filler, and asphalt. The results of the kandora mountain stone aggregate wear test are 26.78%, the combined specific gravity is 2.59. The design of the HRS-WC mixture uses graphical and analytical methods to obtain the aggregate composition of the HRS-WC asphalt mixture that meets the specifications, so that the optimum plan asphalt content (Pb) is 6.5%. 7%, 7.5%, 8%, 8.5% with KAO value of 7%. The number of test specimens was 30 samples using asphalt penetration 60-70. The results of conventional marshall testing research with Pb 7.5% are density 2.30, VIM 3.29%, VMA 17.53%, FVB 81.22%, stability 880.96 kg, flow 2.93, and marshall Quotient 302.60. Testing fine aggregate variation with KAO using 20% sand mixture obtained density 2.27, VIM 4.85%, VMA 18.41%, FVB 73.66%, stability 653.88kg, flow 3. 37, and marshall quotient 195.69, 50% sand mixture obtained density results 2.27, VIM 4.85%, VMA 18.41%, FVB 73.66%, stability 653.88kg, flow 3.37, and marshall quotient 195.69 The remaining marshall strength index test was obtained at 91.01%. Based on the results of aggregate characteristics testing and Marshall testing, the Kandora Kandora Mountain stone meets the 2018 Bina Marga specifications for HRS-WCHot Rolled Sheet (HRS) mixtures are one type of hot asphalt mixture consisting of a mixture of fine aggregate, coarse aggregate, filler, and asphalt.